Enzyme histochemistry of oxidoreductases in small intestine of buffalo foetii - ROY, K S; SINGH, OPINDER; KUMAR, ANOOP (The Indian Journal of Animal Sciences, 2011)
This study was planned to record the distribution pattern of the oxidoreductases in small intestine of buffalo foetuses during prenatal development. Succinic dehydrogenase, lactate dehydrogenase, glucose-6-phosphate dehydrogenase, reduced nicotinamide adenine dinucleotide phosphate-diaphorase (NADPH-D), reduced nicotinamide adenine dinucleotidediaphorase (NADP-D) and non-specific esterases, were studied. The activity was better delTIonstrable in lamina epithelialis and tunica muscularis of small intestine.Â